2014
DOI: 10.1117/1.jmi.1.3.034502
|View full text |Cite
|
Sign up to set email alerts
|

Manually segmented template library for 8-year-old pediatric brain MRI data with 16 subcortical structures

Abstract: Abstract. Manual segmentation of anatomy in brain MRI data taken to be the closest to the "gold standard" in quality is often used in automated registration-based segmentation paradigms for transfer of template labels onto the unlabeled MRI images. This study presents a library of template data with 16 subcortical structures in the central brain area which were manually labeled for MRI data from 22 children (8 male, mean age ¼ 8 AE 0.6 years). The lateral ventricle, thalamus, caudate, putamen, hippocampus, cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This segmentation method has already been shown to provide high quality segmentation for segmentation of caudate, thalamus, putamen, and hippocampus (average dice coefficient = 0.85). Another validation study in the context of segmentation of pediatric MRI images found the dice coefficients of 0.89 for thalamus, 0.89 for caudate and 0.87 for putamen, thereby emphasizing accurate segmentation results (Garg et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This segmentation method has already been shown to provide high quality segmentation for segmentation of caudate, thalamus, putamen, and hippocampus (average dice coefficient = 0.85). Another validation study in the context of segmentation of pediatric MRI images found the dice coefficients of 0.89 for thalamus, 0.89 for caudate and 0.87 for putamen, thereby emphasizing accurate segmentation results (Garg et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of templates for segmentation is known to impact segmentation quality (Garg et al, 2014 ). In our study, we used templates ( n = 6) from the UBC cohort which were manually segmented by a neuro-anatomy expert.…”
Section: Discussionmentioning
confidence: 99%